A risk as an infection route: Nasal colonization of methicillin-resistant Staphylococcus aureus USA300 clone among contact sport athletes in Japan. Issue 8 (August 2020) - Moriya, Mariko; Tsurukiri, Junya; Nakaminami, Hidemasa; Yamanaka, Hiroshi; Kobayashi, Takehito; Tsubouchi, Nobuhiko; Yokomori, Ryohei; Takadama, Shunsuke; Noguchi, Norihisa; Matsumoto, Tetsuya; Arai, Takao
Abstract: Panton-Valentine leukocidin (PVL)-positive USA300 clone is a highly pathogenic and global epidemic community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) clone. Athletes are particularly vulnerable to CA-MRSA infection because of the frequency of skin trauma, close-contact situations, and sharing of equipment that is customary in the athletic setting. We experienced a case of Japanese collegiate football player with septic pulmonary emboli secondary to infectious iliofemoral deep venous thrombosis caused by the USA300 clone. Here, we screened the nasal carriage of USA300 clone colonization among asymptomatic teammate of the patient to elucidate the infection route. Among 69 nasal samples, CA-MRSA strains were found in 5.8% (four samples). Molecular epidemiological analyses showed that three of the CA-MRSA strains were USA300 clone. Furthermore, pulsed-field gel electrophoresis revealed that all nasal USA300 clones showed 100% identity with the USA300 clone isolated from their teammate with critical infection. Our findings indicate that nasal colonization of the PVL-positive CA-MRSA, especially USA300 clone, pose a threat among contact sport athletes in Japan likewise other countries. An immediate infection control strategy for contact sport athletes is necessary to prevent outbreaks of PVL-positive CA-MRSA infections.